Multiculturalism and Gender Equality in Vocational High Schools in Yogyakarta: A Phenomenological Study - Roviana, Sri; Kistoro, Hanif Cahyo Adi; Kodriati, Nurul; Yusutria, Yusutria; Long, A. Sunawari (International Journal of Social Learning (IJSL), 2025)
Multiculturalism is the most appropriate term to describe diversity in schools. Ethnic, religious, racial and gender diversity are recognized in educational practices involving teachers and students. This article aims to analyze the practice of multiculturalism in schools, exploring the various driving factors and barriers faced by teachers and students. This descriptive research used a phenomenological approach, data was obtained from 35 students and teachers using interviews and Google Forms. Data were analyzed by reduction, description, and conclusion based on the identification of significant themes. The main areas of multicultural categorization in vocational high schools: gender equality in educational practices, differences between rural and urban geographical backgrounds, socio-economic disparities, and educational content provided by educators. Muhammadiyah schools in Yogyakarta do not seem to have optimally implemented gender-equity-based multiculturalism. This study highlights the gender injustice to societal constructs, economic disparities that affect educational experiences, and geographical background of students.